BID vs TID dosing of unfractionated heparin for venous thromboembolism (VTE) prophylaxis in hospitalized patients. Issue 3 (March 2015) - Noble, Melissa; Lyon, Corey
Abstract : Case : A 64‐year old man with a history of COPD presents with worsening shortness of breath, 5 days of cough, increase sputum production, malaise, and fever. Vitals are significant for tachypnea (rate 28 bpm), and hypoxia (82% on room air). His BMI is 41. Physical exam reveals no JVD or lower extremity edema, but prominent expiratory wheezes bilaterally. Chest radiography reveals hyperinflated lungs. Writing your admission orders for a COPD flare, you wonder if the patient should receive BID or TID dosing of subcutaneous unfractionated heparin for VTE prophylaxis.